Generalized Model Predictive Pulse Pattern Control Based on Small-Signal Modeling-Part 2: Implementation and Analysis - Dorfling, Tinus; Mouton, Hendrik du Toit; Geyer, Tobias (IEEE transactions on power electronics, 2022)
A newly proposed model predictive pulse pattern controller, which is applicable to higher-order converter systems, is implemented on a low-cost field-programmable gate array. It is shown that how the computations of the underlying quadratic program of the control algorithm can be reduce, thus enabling a resource-efficient implementation. The implemented control algorithm is evaluated via hardware-in-the-loop simulations. The results show that the proposed controller achieves a short settling time during transients and the superior harmonic performance of optimized pulse patterns during steady-state operation.